Comprehension of novel metaphor in young children with Developmental Language Disorder. (December 2018) - Bühler, Daniela; Perovic, Alexandra; Pouscoulous, Nausicaa
Background and aims: Difficulties with aspects of morphosyntax, phonology and/or vocabulary are the hallmark of Development Language Disorder (DLD). Yet, little is known about the linguistic-pragmatic abilities of young children with DLD. Previous studies suggest that children with DLD are experiencing difficulties with idioms, sayings and slang expressions, often interpreting them in a literal or unconventional fashion. However, it is unclear whether this is caused by difficulties to make pragmatic inferences in general or whether it stems from their semantic abilities. We therefore investigated novel metaphor understanding in young children with and without DLD. Methods: We assessed novel metaphor comprehension using a reference assignment task with 15 children with DLD diagnoses (ages 42–49 months) as well as typically developing peers matched on chronological age (n = 15) and on language (n = 15). Results: Children with DLD performed worse than their age-matched peers but in a comparable manner to the (younger) language-matched typically developing children. Performance was not related to non-verbal intelligence in the children with DLD. Conclusion: The findings indicate that young children with DLD have difficulties with metaphor comprehension but also suggest that these difficulties are in line with their general language difficulties and linked to their overall linguistic competence rather than reflecting additional specific issues with deriving pragmatic inferences. Implications: Our study adds to a growing body of literature showing that children with low language abilities are also likely to display more difficulties in understanding figurative language independently of any other symptomatology of their clinical diagnosis. It also supports the argument that deficits in the pragmatic domain are a secondary impairment rather than a core deficit in children with DLD. Nonetheless, children with DLD do show difficulties in understanding metaphors. Understanding figurative language is necessary for everyday communication and should therefore be targeted alongside traditional treatments by clinicians treating children with DLD.